Dealing with the media : a handbook for students, activists, community groups and anyone who can't afford a spin doctor - Rau, Chris (University of New South Wales Press, 2010)
Drawing from over two decades of journalism and media experience, this practical guide offers easy-to-follow advice on how to deal with the media--both traditional and electronic. With tips from Australian leaders in the field, such as Phillip Adams and David Marr, this thorough manual addresses a variety of issues, including how to develop a relationship with journalists, how to deal with being the center of a news story, and how to join the online media revolution. Students, activists, community groups, and businesses will greatly benefit from this essential overview.